Collaborative Government in Poverty Reduction Through Learning Forum and Its Impacts for NGOs in Surakarta, Indonesia - Haryani Saptaningtyas; Drajat Tri Kartono; Akbarudin Arif; Sapja Anantanju (Journal of Government and Civil Society, 2025)
Synergism between the government and Non-Government Organizations (NGOs) through a learning forum in order to apply the policy of Self-Management  III is highly necessary for the alleviation of poverty in the City of Surakarta, Central Java, Indonesia. However, this policy has impacted the way NGOs operate in the field. The terminology of non-government organizations in Indonesia is analogized with the private sector and is also positioned as one of the third sector development by Helmut K. Anheier (2000). Under the terminology of CSOs, a non-government is recognized as one of the partner institutions of the government. Indonesia President Regulation (Perpres) number 16 of 2018, junto number 12 of 2021 concerning Government Procurement of Goods/Services provides a collaborative model. This paper discusses how policy is implemented at the local level by the Learning Forum. Data analysis was carried out in stages: selecting data, coding data, and compiling meta-descriptive analytics. This paper argues that collaborative government depends on the diverse actors of NGOs and their points of view on government policy. Some NGOs perceive this regulation as a prospectus solution regarding financial issues, while other NGOs think it would impact the independence of the institution. Therefore, regulation also presents a force factor in developing a collaboration between civil society and government in eradicating urban poverty, as well as a new challenge related to repositioning NGOs/CSOs itself. Sinergisme antara pemerintah dan Lembaga Swadaya Masyarakat (LSM) melalui kebijakan Swakelola III telah diterapkan  oleh pemerintah melalui Peraturan Presiden (Perpres) Indonesia nomor 16 tahun 2018, junto nomor 12 tahun 2021 tentang Pengadaan Barang/Jasa Pemerintah memberikan model kolaboratif yang berdampak pada internal LSM, meskipun tujuannya adalah untuk mempercepat penanggulangan kemiskinan. Terminologi lembaga swadaya masyarakat di Indonesia dianalogikan dengan sektor swasta dan juga diposisikan sebagai salah satu sektor ketiga pembangunan oleh Helmut K. Anheier (2000). Di bawah terminologi lembaga swadaya masyarakat (LSM) diakui sebagai mitra pemerintah. Tulisan ini membahas bagaimana kebijakan pemerintah diimplementasikan di tingkat lokal oleh Forum Belajar. Analisis data dilakukan secara bertahap: memilih data, mengkodekan data, dan menyusun analisis meta-deskriptif. Pelaksanaan peraturan ini bergantung pada cara pandang actor LSM. Sebagian actor menganggap peraturan ini menjadi solusi untuk masalah keuangan sebagian LSM, tetapi sebagian LSM yang lain menganggap peraturan ini berdampak pada independensi lembaga. Dengan demikian disatu sis perpres menjadi upaya pendorong kolaborasi pemerintah dan LSM, sekaligus mereposisi LSM itu sendiri.